2012
DOI: 10.2217/rme.12.25
|View full text |Cite
|
Sign up to set email alerts
|

Cell Therapy with Adipose Tissue-Derived Stem/Stromal Cells for Elastase-Induced Pulmonary Emphysema in Rats

Abstract: Not only HGF, but also CINC-1, secreted from transplanted and viable ASCs presumably contributed to lung repair through angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…ASCs secrete angiogenic growth factors such as HGF and VEGF [16], which have already been reported to contribute to functional recovery and tissue repair after SCI through angiogenetic and antiapoptotic activity [24,25]. Our study also showed that ASCs secreted abundant growth factors after pre-incubation with bFGF in vitro.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…ASCs secrete angiogenic growth factors such as HGF and VEGF [16], which have already been reported to contribute to functional recovery and tissue repair after SCI through angiogenetic and antiapoptotic activity [24,25]. Our study also showed that ASCs secreted abundant growth factors after pre-incubation with bFGF in vitro.…”
Section: Discussionsupporting
confidence: 75%
“…However, the intravenous infusion of ASCs into SCI rats produced little increase in these growth factors in the injured spinal cords. Systemic transplantation of ASCs in rats with elastase-induced pulmonary emphysema enhanced the HGF expression in the lung tissue [16]. Indeed, we found that ASCs accumulated in the lungs at a high level, perhaps accounting for the high HGF levels observed in the pulmonary emphysema model, but not in the SCI model.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In one study of C57BL/6 mice, intratracheal elastase administration produced a greater amount of low-density areas than CS exposure, as observed on quantitative micro-computed tomography [70]. A wide variety of studies have highlighted the proteolytic activity of elastase in causing structural changes, such as higher mean linear intercept and alveolar enlargement both in mice [71][72][73][74][75] and in rats [76][77][78][79] (Table 2). Furthermore, several studies reported changes in ECM composition after elastase administration, such as disorganized elastin [80,81], degradation of proteoglycans [82], and abnormal collagen remodeling [83][84][85][86][87][88].…”
Section: Elastase Instillationmentioning
confidence: 99%
“…Reduced body mass, time-dependent decrease in muscle mass, type I oxidative fibers, and muscle cross-sectional area Braber et al, 2010 [62] A/J mice Animals exposed to CS 5 days/ week for 20 weeks Right ventricle hypertrophy [77] Wistar rats Single intratracheal injection of elastase Alveolar enlargement, reduced arterial oxygen tension Bianchi et al, 2015 [78] Boiati et al, 2010 [79] Wistar rats Single intratracheal injection of elastase Higher mean linear intercept Table 2 Models of emphysema induced by elastase.…”
Section: Gosker Et Al 2009mentioning
confidence: 99%